2008
DOI: 10.1261/rna.1029808
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy of the genetic code and stability of the base pair at the second position of the anticodon

Abstract: With an analysis of the structural constraints of the anticodon-codon interaction within the decoding center of the ribosome, we show that the extent of degeneracy at the third position of the anticodon is determined by the level of stability of the base pair at the second position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 31 publications
1
82
0
1
Order By: Relevance
“…It has also been suggested to occur in chloroplasts (Shinozaki et al, 1986) and supported by in vitro experiments using wheat (Triticum aestivum) germ extracts and bean (Phaseolus vulgaris) chloroplast tRNAs (Pfitzinger et al, 1990). Further analysis showed that two out of three critically depends on the stability of the second base pair formed between the codon and anticodon and that this stability is influenced by the structure of the tRNA anticodon loop (Lehmann and Libchaber, 2008).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has also been suggested to occur in chloroplasts (Shinozaki et al, 1986) and supported by in vitro experiments using wheat (Triticum aestivum) germ extracts and bean (Phaseolus vulgaris) chloroplast tRNAs (Pfitzinger et al, 1990). Further analysis showed that two out of three critically depends on the stability of the second base pair formed between the codon and anticodon and that this stability is influenced by the structure of the tRNA anticodon loop (Lehmann and Libchaber, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…This tRNA lacks a uridine at position 34 required for superwobble but can form the strong Watson-Crick pairing at positions 35 and 36 (Figure 1) required to stabilize codon-anticodon pairing when there is a mismatch at the third position (Lehmann and Libchaber, 2008). However, tobacco cptRNA Gly (GCC) is apparently unable to decode by two out of three, despite that positions 2 and 3 of the anticodon are cytidines (Rogalski et al, 2008).…”
Section: Two Out Of Three Decoding Probably Occurs In Chloroplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a molecular mechanism was reported explaining this pattern based on hydrogen bonding interactions (Lehmann and Libchaber 2008). When the first two nucleotides of a codon form six hydrogen bonds with the anticodon, the codon box is a family box (codons CCN, CGN, GCN, and GGN).…”
Section: Wobble Rules and Family Boxesmentioning
confidence: 99%
“…When the first two nucleotides of a codon are able to make five hydrogen bonds with the anticodon, the codon box is a family box only if the middle base of the codon is a pyrimidine (codons UCN, CUN, ACN, and GUN). This is caused by the stabilization of the position of the purine that forms the middle base of the anticodon by a long-range intramolecular hydrogen bond from U 33 (Lehmann and Libchaber 2008).…”
Section: Wobble Rules and Family Boxesmentioning
confidence: 99%